Dental Plaque Accumulation and Periodontal Treatment Needs of Smokers - Wulandari, Pitu; Nurhikmawati, Neneng; Sembiring, Juita; Gabrina, Gebby (Dentika: Dental Journal, 2023)
Organic deposits such as food residue, pellicle, dental plaque, and calculus can easily stick to the surface of smokers' teeth due to the tar content that sticks to the teeth, causing the tooth surface to become rough. This study aims to describe periodontal conditions through plaque accumulation and the need for periodontal treatment in smokers. Cross-sectional study at the Dental and Oral Hospital, University of North Sumatra, with a sample of 60 smokers. Plaque accumulation examination uses the Loe and Silness index and periodontal status needs use the Community Periodontal Index of Treatment Needs (CPITN) index. The results of the periodontal status of smokers showed that 36.7% of smokers had a periodontal status score of 0 (healthy periodontium), 33.3% had a periodontal status score of 2 (supragingival calculus), 28.3% had a score of 1 (spontaneous bleeding) and 1.7 % had periodontal status with a score of 3 (pockets 4-5 mm). The results showed that 36.7% did not need treatment (TN 0), 35% of smokers needed better dental care at home/improved oral hygiene and tartar cleaning (TN II), and 28.3% of smokers only needed adequate dental care. better (TN I). The conclusion of this study is that the periodontal treatment needs of smokers at RSGM USU are based on the number of cigarettes and duration of smoking, which is most often found in periodontal status and treatment with scores of 0 and 2.